Giới thiệu mô hình“chia nhóm học tập trực tuyến bằng kĩ thuật trải nghiệm đóng vai” ở nhà trường phổ thông - Bùi Thế , Hường (Tạp chí Giáo dục, 2021)
In order to have effective online teaching and learning, we need to implement many new active teaching methods. One method that has been effectively applied is online learning through home lectures before class, incorporating role-playing techniques in IT practical lessons. The article introduces the online learning model using the role-playing technique in high school. In this method, students experience the role of an instructor as a teacher in the class to transmit the content and manipulation in a practice period to their classmates. Thereby, students can firmly grasp and inculcate personal knowledge while achieving theoretical and practical knowledge. Role plays also help them develop communication skills, knowledge arrangement, self-study and group work.